2016
DOI: 10.7146/kok.v44i122.25049
|View full text |Cite
|
Sign up to set email alerts
|

Enquete

Abstract: Kritik i dag

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Moreover, dispersal via vegetative fragments is well documented in freshwater flora. Sand-Jensen et al [12] found that 90% of new macrophyte patches in streams developed from the vegetative fragments that settled in a new area. In their review, De Meester et al [16] corroborated this finding with examples from other plant and animal species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, dispersal via vegetative fragments is well documented in freshwater flora. Sand-Jensen et al [12] found that 90% of new macrophyte patches in streams developed from the vegetative fragments that settled in a new area. In their review, De Meester et al [16] corroborated this finding with examples from other plant and animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Settlement of the dispersed asexual propagules has been confirmed in several taxa: plants in lentic habitats [16], in streams [12,17,18], marine macrophytes [19,20], freshwater bryozoans [21], moss [22], sea anemones [23], corals [14,24] and sponges [11], among others. Post dispersal establishment of fragments of submerged freshwater macrophytes is well supported [12,25,26]. Studies which looked into this process in marine macrophytes reported successful establishment [19,20,27–30].…”
Section: Introductionmentioning
confidence: 99%